To divide the polynomial \( x^3 - a^3 \) by \( x - a \), we can use polynomial long division or recognize it as a difference of cubes. The general factorization of a difference of cubes \( x^3 - a^3 \) is given by:
\[ x^3 - a^3 = (x - a)(x^2 + ax + a^2) \]
Thus, when we divide \( x^3 - a^3 \) by \( x - a \), we get:
\[ x^3 - a^3 = (x - a)(x^2 + ax + a^2) \]
This matches with our options. The correct polynomial identity established is:
\[ x^3 - a^3 = (x - a)(x^2 + ax + a^2) \]
Therefore, the correct response is:
x³−a³=(x−a)(x²+ax+a²)